THE BENEFITS OF IMAGES: GUESS AND CHECK GAME IN MATH CLASSROOM - Yanuarto, Wanda Nugroho (PEOPLE: International Journal of Social Sciences, 2015)
Geometry is a learning that requires some abilities to cover it. One of it is the spatial ability. The purpose of this study are how learning geometry in mathematics education, Teacher Training and Education Faculty at the University of Muhammadiyah Purwokerto, Indonesia can be easily understood by students. So, the researchers made a model of learning that is associated with the game, guess and check game is one of a game which is support for the student to understand the geometry with easily. Guess and check game consists of several steps or rules of the game. Guess and Check game also closely associated with the image. To improve a spatial ability and motivation to learn geometry for students, images are needed in the game especially in guess and check game. How guess and check the game as the application of the use of the image can improve spatial ability and motivation to learn in geometry?